Two-staged hybrid treatment of persistent atrial fibrillation: short-term single-centre results - Kurfirst, Vojtěch; Mokraček, Aleš; Bulava, Alan; Čanadyova, Júlia; Haniš, Jiři; Pešl, Ladislav (Interactive cardiovascular and thoracic surgery, 2014)
OBJECTIVES: The treatment of persistent and long-standing persistent atrial fibrillation (AF) has unsatisfactory results using both medical therapy and/or catheter ablation, where incomplete ablation lines remain a significant problem. This study evaluates the feasibility, efficacy and safety of the sequential, two-staged hybrid treatment combining thoracoscopic surgical and transvenous catheter AF ablation. METHODS: Thirty patients with persistent and long-standing persistent AF underwent surgical thoracoscopic radiofrequency (RF) ablation procedure using a predefined protocol (pulmonary veins isolation, box lesion, isthmus line lesion, dissection of the ligament of Marshall, left atrial appendage exclusion with an epicardial clip and ganglionated plexi ablation) followed by diagnostic catheterization and RF ablation 3 months later. In this session, electrical mapping of the left atrium was performed and any incomplete isolation lines were completed. Mitral and cavotricuspid isthmus ablation lines were performed during this session as well. RESULTS: The preoperative mean duration time of AF was 33 ± 27 months with 17% patients with persistent and 83% patients with long-standing persistent AF. The mean size of the left atrium was 48 ± 5 mm. The complete surgical ablation protocol was achieved in 97% of patients, with no death, and no early stroke or pacemaker implantation in the early postoperative period. In 63% of patients, the left atrial appendage was excluded with an epicardial clip. An endocardial touch-up for achievement of bidirectional block of pulmonary veins was necessary in 10 patients (33%) and on the box, (roof and floor) lesions in 20 patients (67%). Freedom from atrial fibrillation was 77% after surgical ablation and 93% after the completed hybrid procedure. CONCLUSIONS: The sequential, two-staged hybrid strategy (surgical thoracoscopic followed by catheter ablation) is feasible and safe with a high post-procedural success and seems to represent the optimal treatment with low risk load and potentially long-term benefit for patients with a persistent and long-standing persistent form atrial fibrillation.
Keywords: recidiva; Surgical treatment; Humans; torakoskopie; lidé středního věku; studie proveditelnosti; Female; Aged; výsledek terapie; senioři; lidé; Atrial Fibrillation; Hybrid procedure; katetrizační ablace; Radiofrequency ablation; časové faktory; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Recurrence; Thoracoscopy; Feasibility Studies; mužské pohlaví; Catheter Ablation; Atrial fibrillation; Time Factors; Persistent; fibrilace síní